Effects of glucagon-like peptide-2 on TNF-alpha/actinomycin D-induced intestinal epithelial injury: A scannic electron microscopic and immunohistochemical study - (:unkn) unknown (My University, 2011)
Bağırsaktaki endokrin hücrelerden salınan glukagon-benzeri peptid-2 (GLP-2) intestinotrofik aktiviteye sahip peptid yapıda bir hormondur. Bu çalışmanın amacı, tümör nekroz faktör-alfa (TNF-α)/aktinomisin D (Act D) ile ince bağırsakta oluşturulan epitel hasarında GLP-2’nin taramalı elektron mikroskobu ile gözlenen etkilerini incelemekti. Bunun yanı sıra, GLP-2’nin etki mekanizmasının kolesistokinin ve somatostatin gibi gastrointestinal hormonlar aracılı olup olmadığını da aydınlatabilmek amaçlanmıştır. İnce bağırsak epitel hasarı, her fareye intraperitonal olarak 15 μg/kg TNF-α ve 800 μg/kg Act D uygulanması ile oluşturuldu. Hayvanlara TNF-α ve Act D uygulamasından önce 10 gün süreyle her 12 saatte bir subkutanöz olarak 200 μg/kg dozda GLP-2 analoğu enjekte edildi. Taramalı elektron mikroskobu ile yapılan incelemelerde TNF-α/Act D uygulanan farelerin ince bağırsak dokusunda şiddetli epitel hasarı tespit edildi. TNF-α/Act D uygulaması bağırsak mukozasındaki somatostatin immunreaktif endokrin hücre sayısını önemli ölçüde arttırdı, ancak olesistokinin immunreaktif endokrin hücre sayısını değiştirmedi. Öte yandan, GLP-2 ön uygulaması TNF-α/Act D ile oluşturulan ince bağırsak epitel hasarını dejeneratif değişikliklerde ve somatostatin immunreaktif endokrin hücre sayısında belirgin bir azalmaya, kolesistokinin immunreaktif endokrin hücre sayısında ise belirgin bir artışa neden olarak önledi. Sonuç olarak bu çalışma, GLP-2’nin TNF-α/Act D ile ince bağırsakta oluşturulan epitel hasarına karşı koruyucu etkiye sahip olduğunu göstermiştir. Ayrıca, GLP-2’nin koruyucu etkisi kolesistokinin ve somatostatin ile ilişkilendirilebilir.

Glucagon-like peptide-2 (GLP-2) is a peptide hormone with intestinotrophic activity, which is released from the intestinal endocrine cells. The aim of this study was to investigate the effects observed by scanning electron microscope of GLP-2 in intestinal epithelial injury induced by tumor necrosis factor-alpha (TNF-α)/actinomycin D (Act D). In addition, it aimed to elucidate whether the action mechanism of GLP-2 might be mediated by gastrointestinal hormones such as cholecystokinin and somatostatin. The intestinal epithelial injury was induced by intraperitoneal administration of 15 μg/kg TNF-α and 800 μg/kg Act D per mouse. Animals were injected subcutaneously 200 μg/kg GLP-2 analogue every 12 hr for 10 consecutive days prior to the administration of TNF-α and Act D. Scanning electron microscopic examination revealed severe epithelial damage in the small intestine of TNF-α/Act D-administered mice. The administration of TNF-α/Act D was significantly increased the number of somatostatin-immunoreactive endocrine cells, but did not affect the number of cholecystokininimmunoreactive endocrine cells in the intestinal mucosa. On the other hand, GLP-2 analogue pretreatment prevented TNF-α/Act D-induced intestinal epithelial injury by causing a marked decrease in the degenerative changes and the number of somatostatin-immunoreactive endocrine cells, and a significant increase in the number of cholecystokinin-immunoreactive endocrine cells. As a result, the present study indicates that GLP-2 has a protective effect against TNF-α/Act D-induced intestinal epithelial injury. Morever protective effect of GLP-2 might be related to somatostatin and cholecystokinin.
TNF-alfa/aktinomisin D ile oluşturulan ince bağırsak epitel hasarında glukagon-benzeri peptid-2'nin etkileri: Taramalı elektron mikroskobik ve inmunohistokimyasal bir çalışma
Keywords: Biyoloji